Introduction to identity-based encryption - Martin, Luther (Artech House information security and privacy series., 2008)
"For professionals looking to fully understand and effectively implement identity-based encryption (IBE) technology, this authoritative resource is a smart choice. Until now, details on IBE could only be found scattered throughout journal articles and conference proceedings. This unique volume offers complete, easy-to-understand guidance."--Jacket